(384) The Role of Industry in Economic Development دور الصناعة في التنمية الاقتصادية. - Engert, M. (معهد التخطيط القومى, 2024)
This study addresses the importance of industry in making nations wealthy and powerful, a fact that is evident and needs little debate. It highlights the divergence in ideas about achieving rapid industrialization despite consensus on its necessity. The study aims to provide a general background on issues related to industrialization and illustrate some relevant details. A modern economy is fundamentally an industrial one, requiring socio-economic planning to focus on industrial development as a key part of national planning, particularly for developing countries. Development is generally understood as the process of initial industrialization.